2006
DOI: 10.1007/s00383-006-1693-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glutamine-supplemented total parenteral nutrition on nutrition and intestinal absorptive function in a rat model

Abstract: The aim of the present study was to evaluate the effect of short-term (7 days) glycyl-glutamine-supplemented total parenteral nutrition (TPN) on nutrition and intestinal absorptive function in a rat model. Thirty Wistar rats, weighting 140-180 g, were divided into three groups (n=10) randomly. The animals received isonitrogenous and isocaloric TPN solutions for 7 days. The nitrogen was supplied by glycyl-glutamine dipeptide-supplemented amino acid solution (group G), and two standard amino acid solutions (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The mucosal epithelium of the small bowel undergoes a continuous process of proliferation and differentiation, and the administration of GH and GLN might induce complex interactions to affect this process . The interactions between GH and GLN were speculated to be dependent on multiple factors such as the dose or concentration, route of administration, treatment duration, and treatment sequence of GH and GLN . The dose/concentration of GH and GLN may affect the results we report; however, the doses/concentrations of GH and GLN we used for in vitro and in vivo studies were chosen according to previous reports .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mucosal epithelium of the small bowel undergoes a continuous process of proliferation and differentiation, and the administration of GH and GLN might induce complex interactions to affect this process . The interactions between GH and GLN were speculated to be dependent on multiple factors such as the dose or concentration, route of administration, treatment duration, and treatment sequence of GH and GLN . The dose/concentration of GH and GLN may affect the results we report; however, the doses/concentrations of GH and GLN we used for in vitro and in vivo studies were chosen according to previous reports .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Both oral administration and parenteral supplementation of GLN can prevent the mucosal atrophy, promote DNA and protein synthesis in intestinal epithelial cells, increase mucosa weight, and protect mucosal cells from apoptosis in rats. [5][6][7][8] Transgenic mice over-expressing GH showed greater body weight and intestinal weight than control mice. 9 Clinical trials for patients with SBS also revealed that GH increases intestinal absorption of energy, nitrogen, carbohydrates, and fat and helps earlier weaning from PN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamine ingestion during acute dehydration stress is reported to enhance fluid and electrolyte absorption resulting from intestinal disorders [1-3], but it's effects may not be consistent [4]. This is possibly related to stability issues of glutamine in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine has been reported to increase electrolyte and water absorption in both animal and human subjects suffering from intestinal infections [7-9], but not in others [10]. However, differences may be related to the stability issues related to glutamine.…”
Section: Introductionmentioning
confidence: 99%